2021
DOI: 10.3390/ma14247806
|View full text |Cite
|
Sign up to set email alerts
|

Effects of B on the Structure and Properties of Lead-Tin Bronze Alloy and the Mechanism of Strengthening and Toughening

Abstract: High lead–tin bronze is widely used in the selection of wear-resistant parts such as bearings, bearing bushes, aerospace pump rotors, turbines, and guide plates because of its excellent wear resistance, thermal conductivity, fatigue resistance, and strong load-bearing capacity. At present, high lead–tin bronze is used as a material for bimetal cylinders, which cannot meet the requirements of high-strength, anti-wear in actual working conditions under high temperature, high speed, and heavy load conditions, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Instead, it exists as a separate phase. When uniformly dispersed in fine particles between the dendrites, lead maximizes the melting point reduction, improves the fluidity, and increases the wear resistance while maintaining a high mechanical performance [18]. This allows intricate artifacts to be cast with greater ease.…”
Section: Matrix Structure Analysismentioning
confidence: 99%
“…Instead, it exists as a separate phase. When uniformly dispersed in fine particles between the dendrites, lead maximizes the melting point reduction, improves the fluidity, and increases the wear resistance while maintaining a high mechanical performance [18]. This allows intricate artifacts to be cast with greater ease.…”
Section: Matrix Structure Analysismentioning
confidence: 99%
“…Thus, the higher its rate in the ball is, the lower its efficiency is, meaning that it does not fulfil its function [3], [4]. For this reason, some researchers were interested in improving the properties of wear resistance using high-entropy alloys (HEAs) [5], a lead-bronze/steel bimetal composite [6], alumina-toughened-zirconia materials [7], lead-tin bronze alloy [8] etc. Fernández-Álvarez et al [9] revealed that adding nanosilica to milling process makes the epoxy-matrix coatings degrade chemically less than the non-reinforced ones under irradiation and thus wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…As an excellent friction-reduction material, lead-tin bronze (Pb > 5 wt.%), with high strength, high hardness and good wear resistance, is widely used in bimetallic cylinder blocks, bearings, axial shingles, piston pump rotors and other components that require tribological performance [1][2][3][4][5]. Pb exists commonly as a free state on the α-Cu matrix; however, a layer of Pb film will be formed on the worn surface under the friction condition due to the frictional heat production.…”
Section: Introductionmentioning
confidence: 99%